Perioperative acute myocardial infarction in patients after non-cardiac surgery in China: Characteristics and risk factors. Issue 34 (August 2019) - Zhou, Xiaoxin; Chen, Lingke; Su, Zhongxue; Li, Yue; Tu, Mengyun; Xiao, Jie; Pan, Zhiying; Su, Diansan
Abstract : Abstract: To examine the characteristics and short-term outcome of perioperative myocardial infarction (PMI), a single-center retrospective study was carried out. The electronic medical records of 278, 939 patients aged 45 years or older who underwent non-cardiac surgery at Renji Hospital from January 2003 to December 2015 were screened based on diagnostic codes (ICD121, ICD121.0, ICD121.1, ICD121.2, ICD121.3, ICD121.4, or ICD121.9). The incidence and characteristics of PMI and mortality risk factors were analyzed after non-cardiac surgery. PMI was reported in 45 patients, with an incidence rate of 1.61 per 10, 000 and a mortality rate of 75.6% (34/45). The PMI incidence rate increased significantly with age. The PMI incidence rate was the highest for vascular surgery (5.82 per 10, 000 cases). PMI occurs mainly within 48 h of surgery, with most cases showing an onset in the general wards. Logistic analysis showed that the use of nitrates is the independent protective factor for the outcomes of patients with PMI. The incidence of PMI in non-cardiac surgery is approximately 2 of 10, 000 in patients aged 45 years or older, and increased significantly with age. The use of nitrates might be helpful for their survival. Abstract : Supplemental Digital Content is available in the text